O efeito “fungal highway”: mobilidade bacteriana nas hifas de fungos micorrízicos arbusculares - Marascalchi, Matheus Nicoletti (2022)
Bacteria and arbuscular mycorrhizal fungi (AMF) are important components of soil biota and provide fundamental services for plants and the ecosystem; however, bacteria have limitations to move in the soil that can be solved by dislocating through fungal hyphae. The present work aimed to evaluate the bacterial cell’s motility of 6 different species of soil bacteria in the hyphae of an AMF species in in vitro culture. And also to analyze the motility of 4 species of bacteria in hyphae of G. albida associated with seedlings of Trifolium repens. Among the 6 bacteria analyzed, only Pseudomonas sp. and Azorhizobium doebereinerae were able to swim in AMF hyphae, and only Paenibacillus kribensis wasn’t able to colonize G. albida hyphae. Among the 4 species of bacteria analyzed in hyphae of G. albida associated with T. repens, once again, only Pseudomonas sp. and A. doebereinerae were able to migrate through AMF hyphae and did not show significantly greater distances than when inoculated only in fungal hyphae. There were also no significant differences between the colonial advance between symbiotic and non-symbiotic hyphae. This is the third study evaluating bacterial motility in AMF hyphae and the data suggest that the transport relationship of bacteria by hyphae is independent of association with a plant host. These limitations should be explored in future studies, incorporating factors such as motility on non-fungal surfaces, different AMF species and incorporation of soluble nutrient sources through bacterial activity. These incorporations can be made through adaptations in the methodologies developed in this work.